Letramento digital e letramento acadêmico estratégias de navegação e leitura de graduandos em letras - Leila Rachel Barbosa Alexandre (2019)
In the light of the concepts of digital literacy and academic literacy, this research aimed to analyze mobilized skills and strategies used by undergraduates students in Letters of the Universidade Federal do Piauí when they have to read and navigate online to perform academic tasks.. To meet this goal, we built the theoretical framework in order to understand, initially, the concept of literacy (SOARES, 2016 [1998]; STREET, 2014 [1995]) and to enter into discussions related to academic literacy (LEA; STREET, 2006, 1998; STREET, 2010; GEE, 2002; ZAVALA, 2009) and digital literacy (LEU et al, 2013; NG, 2012; RIBEIRO, 2008). Then we discuss the relationship between digital technologies and academic practice and dialogue with studies that deal with reading and navigation in digital environments (COIRO, 2011; PAIVA, 2013; RIBEIRO, 2008, 2012; COSCARELLI; 2002; LEU et al, 2012 ; CASTEK et al, 2012; COSCARELLI; COIRO, 2014) and studies that specifically refer to academic reading (NELSON; HAYES, 1988; HILLESUND, 2010; WILEY et al, 2009). This theoretical basis provided us with subsidies to analyze the research findings, collected from the accomplishment of three stages, with the participation of twenty informants, ten who attended the 6th period and ten who attended the 9th period. In the first stage, a pre-task questionnaire was applied to evaluate students' previous conceptions about academic practices and their texts, as well as their perceptions about the relationship between these practices and digital technologies, especially those dedicated to the searching and reading of texts. In the second stage, the informants accomplished navigation, reading and writing tasks that allowed them to analyze their choices during the journeys they accomplished while searching and reading texts. In the third stage, a post-task questionnaire was applied to obtain information from the students about problems perceived during the accomplishment of the tasks of the second stage. Data from the three stages were related and generated two types of analysis: one from the pre-task questionnaire, about recurrences perceived in both groups, and another from the second stage tasks, related to the other two stages, with analysis of the mobilized skills and strategies used by informants in their navigation and reading paths. Analyzes from the data of the pre-task questionnaires show that, in the 6th period group, there is commonly a more generalizing perception about the academic text and related practices, while in the 9th period group there were more mentions of characteristics more specific to academic literacy practices. The analysis of the perceptions of the informants about academic research activities on the Internet showed concern of both groups with the reliability of the sources and evidenced the most frequent mention of specialized platforms by the 9th period informants. The ways used by the informants observed in the execution of the tasks of the second stage, analyzed together with the data of the first and third stages, show that there is no way to guarantee that skills related to digital literacy or academic literacy, treated separately, are more functional for them so that students can meet their reading goals. Instead, from an integrated and situated perspective, it became clear that both types of literacy are strategically mobilized by students, depending on their repertoire of skills and the navigation and reading paths they choose to follow. We therefore argue that digital literacy practices are subject to the ideological configurations and power relations that lie at the heart of academic literacy practices and that, therefore, there is a need not only for students to be educated about ways of doing academic research on the Internet based on general technical knowledge, but effectively participating in academic literacy practices and receiving explicit instruction in their functioning, so that they can effectively take hold of these practices, including digitally.